JOURNAL OF GOVERNMENT & POLITICS : Interpreting 9/11: The Role of Language and Narrative in the Construction of "American" Identity - Chad Tallman (FISIPOL UMY, 2014)
Follwing the attacks on September 11, 2001 (that killed approximately three thousand people) the United States began waging war abroad, resulting in the deaths of hundreds of thousands of civilians and permanently displacing millions of innocent people.